Optic disc and peripapillary vessel density measured with optical coherence tomography angiography and its associations in Chinese adults: a large population-based study. Issue 10 (20th May 2021) - Zhu, Ming Ming; Choy, Bonnie N K; You, Qi Sheng; Chan, Jonathan Cheuk Hung; Ng, Alex L K; Shih, Kendrick; Cheung, Janice Jing Chee; Wong, Jasper Ka Wai; Shum, Jennifer; Ni, Michael Y; Lai, Jimmy Shiu-Ming; Leung, Gabriel M; et al.
Abstract : Purpose: To investigate the optic disc and peripapillary vessel density, as well as its ocular and systemic associations, in healthy eyes among adult Chinese population. Methods: A population-based cross-sectional eye survey was conducted on Chinese adults residing in Hong Kong. 1891 eyes from 1891 participants who completed 4.5×4.5 mm optical coherence tomography angiography scans were recruited. Among the 1891 eyes, 404 were excluded due to low scan quality, optic disc or retinal disorders and non-Chinese ethnicity. The vessel densities (VDs) at nerve fibre layer plexus (NFLP) at both optic disc and peripapillary were collected for analysis. Multiple linear regression analysis was performed to determine the ocular and systemic associations of NFLP VD. Results: The study included 1487 participants (men: 41.2%) with a mean age of 48.8±15.4 years. The mean NFLP VD of the whole en face image, inside disc and peripapillary region was 53.8%, 42.7% and 60.3%, respectively. In the multivariable model, decreased NFLP VDs were significantly associated with older age, male gender, longer axial length (AL) and lower Signal Strength Index. Conclusions: This large population-based cross-sectional study provided quantitative data of optic disc and peripapillary NFLP VD which may serve as a normative reference for clinical use. Apart from age, gender and AL, the scan signal strength also should be taken into consideration during the assessment of NFLP VD.